The Mediating Role of Task Formulation in Crowdsourcing Environments - Rabes, Karl (Tagungsband zum Doctoral Consortium der WI 2013, 2013)
How to obtain high quality solutions from the crowd is still a mystery (Kazai et al., 2009). The understanding of what factors do - or do not - affect solution quality in crowdsourcing approaches has only just started (Aker et al., 2012). Still, it is claimed that a careful task formulation is crucial (Kittur, Chi and Suh, 2008). This research proposal conceptualizes task formulation as a factor influencing the quality of solutions in crowdsourcing approaches. Accordingly the proposal focuses the following research question: